Gut jet lag: how circadian rhythm disruption undermines the Chrono-Microbiota-Motility axis and induces functional constipation - Li, Jitong; Yu, Keying; Sui, Xiaodan; Deng, Houbo; Leng, Yan; Liu, Tiejun (Frontiers in Nutrition, 2025)
Functional constipation (FC) is a highly prevalent gastrointestinal disorder globally. Its complex and multidimensional pathophysiological mechanisms and the limitations of conventional treatments highlight the urgent need to explore new theoretical frameworks. Chronobiological research reveals that the circadian rhythm system plays a central role in maintaining physiological homeostasis, and rhythm disruption caused by modern lifestyles is becoming a common driving factor for various chronic diseases. The gut microbiota, as a key regulator of host physiology, its intrinsic rhythmicity and synchronization with the host’s biological clock are crucial for gut health. This review systematically integrates cross-disciplinary evidence from chronobiology, microbiology, and gastrointestinal motility. Based on this evidence, we propose and substantiate the Chrono-Microbiota-Motility axis as a novel theoretical framework. This framework unveils a novel pathogenic mechanism: gut jet lag. This term describes a state of desynchronization between host and gut microbiota rhythms. This desynchronization is caused by modern lifestyle factors such as irregular routines, disordered eating times, and nocturnal light exposure. This desynchronization translates into gut dysfunction through three core pathways: disrupted short-chain fatty acid production rhythm weakens intestinal propulsive motility, dysregulation of the intrinsic gut clock inhibits morning high-amplitude contractions, and impaired intestinal barrier function triggers low-grade inflammation and increased sensitivity. Based on this theoretical framework, this paper systematically elucidates the scientific basis of “chronotherapy” as a non-pharmacological intervention strategy, including multi-dimensional synergistic interventions such as time-restricted eating, regular routines, light management, and individualized supplement application. This theory achieves a paradigm shift in the etiological research of FC from material homeostasis to temporal synchronization, providing a new explanatory framework for refractory cases, opening up fundamental treatment pathways, and offering evidence-based guidance for the formulation of modern lifestyle health guidelines. Incorporating the time dimension into FC research and clinical practice represents a key breakthrough in understanding this complex disease. Furthermore, it reflects modern medicine’s shift toward a systemic, individualized, and preventive approach.